Finite element and experimental analyses of cylindrical hole flanging in incremental forming - Hussain, G.; Valaei, H.; Al-Ghamdi, Khalid A.; Khan, B. (Elsevier Science Bv, 2016)
The influence of the size of pre-cut hole of blank on the formability of cylindrical hole flanging in single point incremental forming (SPIF) was studied. The flange is produced in four stages starting from 45 degrees to 90 degrees and employing aluminum as the test material. It is shown that the hole size has significant effects on the stress/strain distribution on the cylindrical flange. The magnitude of hoop strains increases and the flange thickness increases as the hole size increases. Likewise, the von Mises stress reduces with the increasing of hole size. Further, there is a threshold value of hole size (i.e., 80 mm) below which severe stresses occur, which lead to sheet fracturing thus failing the successful forming of cylindrical flange. Moreover, the formability reduces as the hole size is increased above the threshold size. Finally, it is concluded that 80 mm is the threshold size of hole for maximizing the formability of aluminum sheet in incremental hole flanging.
Keywords: hole flanging; single point incremental forming (SPIF); formability; stress; strain; threshold